Standard Motor Sales, located at 610 N. Liberty Street and 611 N. Trade Street in 1932. - Unknown (Forsyth County Public Library, 2008)
Photo made in the 1930s.
Standard Motor Sales, located at 610 N. Liberty Street and 611 N. Trade Street in 1932. The men in front of the business are: Alex P. Jones, Dewey Williard, Jack Witherspoon, Smith Whittington and workers in the company.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth